UAS close range remote sensing for mapping coastal environments - Papakonstantinou, Apostolos; Topouzelis, Kostantinos; Doukari, Michaela (My University, 2017)
Coastline change and marine litter concentration in shoreline zones are two different emerging problems indicating the vulnerability as well as the quality of a coastal environment. Both problems present spatiotemporal changes due to weather and anthropogenic factors. Traditionally spatiotemporal changes in coastal environments are monitored using high-resolution satellite images and manned surveys. The last years, Unmanned Aerial Systems (UAS) are used as additional tool for monitoring environmental phenomena in sensitive coastal areas. In this study, two different case studies for mapping emerging coastal phenomena i.e. coastline changes and marine litter in Lesvos island, are presented. Both phenomena have increasing interest among scientists monitoring sensitive coastal areas. This paper outlines the integration of UAS for data acquisition and Structure from Motion (SfM) pipeline for the visualization of selected coastal areas in the Aegean Sea. The followed UAS-SfM methodology produces very detailed orthophoto maps. This high resolution spatial information is used for mapping and detecting primarily, marine litter on coastal and underwater zones and secondly, coastline changes and coastal erosion. More specific the produced orthophoto maps analyzed through GIS and with the use of the appropriate cartographic techniques the objective environmental parameters were mapped. Results showed that UAS-SfM pipeline produces geoinformation with high accuracy and spatial resolution that helps scientists to map with confidence environmental changes that take place in shoreline zones.
Keywords: Coastal management; Marine litter mapping; UAS; UAV data acquisition; UAV-SfM